Antimicrobial activity of calcium hydroxide associated with a new vehicle (Triethanolamine) - Junior, Jaci Simi; Machado, Ricardo; Stiz, Rafael; Figueiredo, Cristiane; Vansan, Luiz Pascoal; Ferrari, Carlos Henrique; Back, Eduardo Donato Eing Engelke; Silva, Emmanuel João Nogueira Leal (Brazilian Dental Science, 2016)
Objective: The aim of this study was to evaluate the antimicrobial effectiveness of calcium hydroxide associated with a two conventional (anesthetic liquid and olive oil) and a new vehicle (Triethanolamine). Material and methods: Initially, microorganisms were collected from four upper incisors presenting unsatisfactory root canal treatments and persistent apical periodontitis from the same patient using sterile absorbent paper cones placed inside the root canal following initial access and root filling removal. Next, they were grown in a BHI culture medium for 24 h. Afterwards, they were placed in 10 Petri dishes with 3 holes, where different formulations of the medications studied were placed. After 48 and 72 h, readings were taken of the growth inhibition halos. Results: After using Kruskal-Wallis test with significance level of 1% (? = 0.01) it was observed that, calcium hydroxide associated with Triethanolamine, produced results similar to those produced by the anesthetic liquid. Both combinations were superior to the association with olive oil. Conclusion: Considering the results of this in vitro study, it is possible to consider that Triethanolamine can be a viable alternative to be used as a vehicle associated with the calcium hydroxide. Keywords: Vehicles; Calcium hydroxide; Endodontics.